Encyclopedia of weather and climate. Volume I, A-L - Allaby, Michael (New York : Facts on File, 2002)
Volume one of a two-volume set which features maps, charts, photographs, and four thousand cross-referenced entries which discuss a variety of topics related to weather and climate.
"Facts on File science library"--Cover.
Includes index.
Young Adult
Keywords: Climatology -- Encyclopedias; Meteorology -- Encyclopedias; Climate -- Encyclopedias; Meteorology -- Encyclopedias